Strategi Kemnaker dalam Peningkatan Sumber Daya Manusia Berbasis Kompetensi (implementasi penerapan KKNI pada kurikulum politeknik ketenagakerjaan dan Balai Latihan Kerja Lembang) - Mochamad Sarif Hasyim; Aly Taufiq (Multiverse: Open Multidisciplinary Journal, 2022)
This study aims to determine the implementation of the SKKNI in two institutions under the Ministry of Manpower that are engaged in education and training, namely BLK Lembang and the Polytechnic of Manpower. Using descriptive qualitative method with observations, interviews and related documentation review. The results showed that the two institutions had carried out a learning procession with a curriculum based on the SKKNI. In addition, the implementation of a dialectical process in the form of dissemination forums and FGDs that occur in order to formulate and harmonize them between curriculum, courses or materials, as well as competencies which are potential employment opportunities.